Possibility of wastewater treatment using MFC with Ni-Co catalyst of fuel electrode = Możliwość oczyszczania ścieków przy wykorzystaniu mikrobiologicznego ogniwa paliwowego z niklowokobaltowym katalizatorem elektrody paliwowej - Włodarczyk, Paweł; Włodarczyk, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of the problems with microbial fuel cells is a low current density of those energy sources. Nonetheless, it is possible to increase the current density by using the catalyst for fuel electrode (anode) - as long as a low cost catalyst can be found. The possibility of wastewater treatment using the Ni-Co alloy as catalyst for MFC?s is presented in this paper. The alloys were obtained with different concentrations of Co (15 and 50% of Co). The increase of current density with Ni-Co catalyst is approximately 0.1 mA/cm2. So, a fundamental possibility wastewater treatment using the Ni-Co alloy as catalyst for microbial fuel cells was presented.
Keywords: mikrobiologiczne ogniwa paliwowe; oczyszczanie ścieków; katalizator; stop Ni-Co; odnawialne źródła energii; inżynieria środowiska; microbial fuel cell; wastewater treatment; catalyst; alloy Ni-Co; renewable energy sources; environment engineering